Urgensi Kode Etik Profesi Advokat - Mhd Alwin; Ahmad Irpan; Fauziah Lubis (El-Mujtama: Jurnal Pengabdian Masyarakat, 2023)
The Advocate profession is related to the task of serving the community to help solve the legal problems it faces. In carrying out their duties, advocates are guided by the Advocate Law, but legal norms are considered insufficient, because professional advocates are associated with behavior that is often influenced by the moral ethics of advocates in every decision making. For this reason, in carrying out their duties, they still need ethical guidelines as guidelines in carrying out their professional duties. In this regard, defenders of the Professional Code of Ethics are indispensable in guiding the behavior of Advocates in making decisions and ethical behavior. Keywords: Urgency, Code of Ethics, lawyer